2003
DOI: 10.1111/j.0889-7204.2003.02419.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐Type Natriuretic Peptide: a New Tool in the Armamentarium Used to Accurately Diagnose Heart Failure

Abstract: Nearly 5 million Americans have heart failure (HF). Making a correct diagnosis early is an important component in the multifaceted approach to detection and/or treatment of this disease. The US Food and Drug Administration recently approved a point-of-care B-type natriuretic peptide assay to be used in the diagnosis of HF. Nesiritide, a synthetic B-type natriuretic peptide, was also approved for use in decompensated HF. B-type natriuretic peptide is released from the cardiac ventricles in response to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A correlation between BNP serum level and NYHA functional class was also documented by Caboral et al . The authors also indicated the possibility for monitoring results of ambulatory treatment of HF patients by means of BNP determination, since it seems to be a more objective indicator of clinical state than NYHA classification [22]. …”
Section: Discussionmentioning
confidence: 99%
“…A correlation between BNP serum level and NYHA functional class was also documented by Caboral et al . The authors also indicated the possibility for monitoring results of ambulatory treatment of HF patients by means of BNP determination, since it seems to be a more objective indicator of clinical state than NYHA classification [22]. …”
Section: Discussionmentioning
confidence: 99%